USING OF UNIFIC CLINICAL PROTOCOLS AS STANDARTS OF MEDICAL CARE IN TEACHING INTERNAL MEDICINE FOR PHYSICIANS INTERNS - Кулаєць, В. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Preparation of interns at postgraduate stage should consider requirements on national medical education (unific clinical protocols) and requires in-keeping standards of medical education to international standards, the implementation of the principles of evidence-based medicine. The goal of unified clinical protocols of medical care is to organize the provision of skilled care to patients with various therapeutics diseases for reducing disability, mortality and reduce quality of life and disability of patients. Department staff therapy and family medicine of postgraduate education does special orientation in order to help interns to combine clinical thinking with modern laboratores and instrumental methods of examination the direction in preventive therapy for preventing polypharmacy and compliance with medical ethics and deontology.